School-Based Drug Prevention What Kind of Drug Use Does It Prevent? - Caulkins, Jonathan P. (RAND Corporation, 2002)
School-based drug prevention, popular with the public and politicians alike, is now a nearly universal experience for American youth. Analysis has shown that the best programs can reduce use of a wide range of substances. But questions remain regarding how to think about and, hence, fund, these programs. Should they be viewed principally as weapons in the war against illicit drugs, or, at the other extreme, do prevention programs benefit students and society most by reducing use of alcohol and tobacco? The authors address these questions by comparing for the first time the social benefits of school-based prevention programs' long-run impacts on a diverse set of different substances.